Analysis of adenylate cyclase activity in Japanese children with orthostatic dysregulation - Nobuyoshi Sugiyama; Tomoyoshi Komiyama; Kengo Ayabe; Shin-ichi Matsuda; Mayumi Enseki; Mariko Ikegami; Yoshihiro Miyashita; Ayumi Sasaki; Yuka Kitamura; Atsushi Uchiyama (PLoS ONE, 2026)
The aim of the study was to clarify the cause of orthostatic dysregulation in Japanese children by analyzing fluctuations in adenylate cyclase activity. Four types of orthostatic dysregulation in Japan include postural orthostatic tachycardia syndrome, delayed orthostatic hypotension, immediate orthostatic hypotension, and vasovagal syncope. However, the exact cause of these disorders remains unknown. To identify the cause of these conditions, we examined the resting blood adenylate cyclase activity and basic clinical data (blood pressure, pulse rate) of 30 patients diagnosed with orthostatic dysregulation (21 postural orthostatic tachycardia syndrome, eight delayed orthostatic hypotension, one immediate orthostatic hypotension, zero vasovagal syncope) and 20 previously reported healthy adults. The results of this study showed that adenylate cyclase activity (isoproterenol and adrenaline) in patients with postural orthostatic tachycardia syndrome was significantly higher than that in patients with delayed orthostatic hypotension and healthy adults. Moreover, patients with postural orthostatic tachycardia syndrome had significantly higher values than healthy adult controls at all five concentration points. Adenylate cyclase activity in patients with delayed orthostatic hypotension showed a trend toward higher values at 10 μM of adrenaline. Furthermore, owing to the higher adenylate cyclase activity in patients with postural orthostatic tachycardia syndrome, their systolic blood pressure was higher than that in patients with delayed orthostatic hypotension. These results suggest that increased adenylate cyclase activity may be related to the onset of orthostatic dysregulation (postural orthostatic tachycardia syndrome and delayed orthostatic hypotension). In conclusion, adenylate cyclase activity levels may be related to the onset of orthostatic dysregulation, and this can be used as a new strategy for diagnosing orthostatic dysregulation.